TINDAK TUTUR EKSPRESIF INTERAKSI GURU DAN SISWA PADA PEMBELAJARAN BAHASA INDONESIA SMP NEGERI 3 X KOTO SINGKARAK TAHUN AJARAN 2022/2023 - Zahara, Regina; Marta, Redo Andi; Putri, Mega (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2023)
This research is motivated by the existence of teacher speech acts in teaching and learning interactions which greatly influence student learning activities, encourage changes in behavior and provide language experience for students. Middle school students were chosen as research tools because middle school students are teenagers who have a lot of expression when communicating. The communication carried out by teachers and students during the teaching and learning process is of course based on the conditions felt by the teacher and students. This research aims to describe the expressive speech acts of teacher and student interactions in Indonesian language learning at SMP Negeri 3 This type of research is qualitative, with descriptive methods. The data collection technique used is (1) The researcher records teacher and student speech during the learning process, until the data obtained is sufficient, (2) The recording results are transcribed from spoken language into written language. The data sources for this research are teachers and students in the teaching and learning process at SMP N 3 Based on the results of research on expressive speech acts of teacher and student interaction in Indonesian language learning at SMP Negeri 3 X Koto Singkarak, researchers found 87 data on expressive speech acts. Expressive speech acts in the form of anger were found in 39 data, expressive speech acts in the form of surprise were found in 10 data, expressive speech acts in the form of resignation were found in 2 data, expressive speech acts in the form of happiness were found in 5 data, expressive speech acts in the form of disgust were found in 4 data, Expressive speech acts in the form of hate were found in 1 data, expressive speech acts in the form of admitting were found in 21 data, expressive speech acts in the form of congratulations were not found in speech acts, expressive speech acts in the form of pity were found in 5 data. Of all the expressive speech acts found, the most frequently found were expressive speech acts in the form of anger. Anger occurs because the expected situation does not match reality.